Preparation method of a nickel-iron-manganese oxide precursor and a sodium-ion layered oxide positive electrode material

CN121627073BActive Publication Date: 2026-10-23ZHEJIANG NATRIUM ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511759548.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-27
Publication Date
2026-10-23
Estimated Expiration
2045-11-27

AI Technical Summary

Technical Problem

但是共沉淀法制备镍铁锰前驱体存在废液处理成本高、元素沉淀不完全,制造过程复杂等问题

Benefits of technology

(1)该镍铁锰氧化物前驱体制备钠离子层状氧化物正极材料,相较与传统的氢氧化物前驱体制备正极材料,步骤简单易操作,反应条件温和,制造成本相对低廉,且制得的产物性能优异,适合规模化生产应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121627073B_ABST
    Figure CN121627073B_ABST
Patent Text Reader

Abstract

The application discloses a kind of nickel iron manganese oxide precursor and preparation method of sodium ion layered oxide positive electrode material, belong to sodium ion battery material technical field, including the following steps: nickel source, iron source and manganese source are mixed according to mole ratio, at least two of the nickel source, iron source and manganese source are metal organic framework material, obtain first mixture;Then first mixture is sintered under the condition of 400~850 DEG C under air atmosphere, 4~8h is prepared nickel iron manganese oxide precursor;The nickel iron manganese oxide precursor prepared in the preceding is mixed with sodium source, blend T according to mole ratio;Second mixture is obtained, then second mixture is sintered under the condition of 500~1000 DEG C under air atmosphere, 15~30h is prepared sodium ion layered oxide positive electrode material, and the material has good specific capacity and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery material technology, specifically a method for preparing a nickel-iron-manganese oxide precursor and a sodium-ion layered oxide cathode material. Background Technology

[0002] Sodium-ion batteries, with their abundant sodium resources, low-temperature performance, and excellent fast-charging capabilities, have shown great application potential in large-scale energy storage, electric vehicles, and other portable devices, and have received widespread attention in recent years. Layered oxide cathode materials for sodium-ion batteries, due to their high theoretical specific capacity and relatively stable structure, have become one of the key research directions. However, traditional layered oxide cathode materials currently face many challenges in practical applications, one key issue being that the average cost per watt-hour of sodium-ion batteries remains relatively high compared to lithium-ion batteries.

[0003] Studies have shown that sodium-ion layered oxide cathode materials, as a crucial component of sodium-ion batteries, account for 30% of the cost, while precursors, another important component of sodium-ion layered oxide cathode materials, account for 40% of the cost of the cathode material itself. Furthermore, the morphology and structural characteristics of the precursor play a decisive role in the performance of the cathode material. Due to the inheritance relationship between the precursor and the cathode material and the large cost proportion of the precursor, developing high-performance, low-cost precursor and cathode material preparation processes is particularly important for improving the performance and reducing the cost of sodium-ion batteries. The traditional method for preparing layered oxide cathode material precursors is the co-precipitation method. Co-precipitation precursors have the advantages of uniform metal ions and high purity of the mixed phase. For example, patent CN120483286A discloses a method for manufacturing a nickel-iron-manganese hydroxide precursor, specifically involving dissolving nickel sulfate, ferrous sulfate, and manganese sulfate in deionized water in a specified ratio, then feeding a mixed solution of sodium hydroxide and ammonia into a reaction vessel to obtain a base liquid, and preparing the nickel-iron-manganese hydroxide precursor under controlled reaction conditions at a certain temperature. However, the co-precipitation method for preparing nickel-iron-manganese precursors has problems such as high waste liquid treatment costs, incomplete element precipitation, and complex manufacturing process.

[0004] In summary, there is an urgent need for a method to prepare nickel-iron-manganese oxide precursors and sodium-ion layered oxide cathode materials to solve this problem. Summary of the Invention

[0005] The first objective of this invention is to provide a method for preparing a nickel-iron-manganese oxide precursor with better specific capacity and cycle performance.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a nickel-iron-manganese oxide precursor includes the following steps: mixing a nickel source, an iron source, and a manganese source in a molar ratio, wherein at least two of the nickel source, iron source, and manganese source are metal-organic framework materials to obtain a first mixture; and then sintering the first mixture in an air atmosphere at 400–850°C for 4–8 hours to obtain the nickel-iron-manganese oxide precursor.

[0007] The prepared nickel-iron-manganese oxide has the following structural formula: Ni x Fe y Mn z O2(x+y+z=1).

[0008] Further settings are as follows: The nickel source is selected from one or more of the following: nickel-based metal-organic framework materials, nickel tetroxide, nickel trioxide, nickel suboxide, basic nickel oxide NiO(OH), nickel hydroxide, nickel suboxide, nickel subsulfate, nickel sulfate, nickel nitrate, nickel acetate, nickel nitrate nonahydrate, nickel subnitrate, nickel chloride, nickel bromide, nickel phosphate, nickel phosphite, nickel carbonate, nickel oxalate, nickel suboxalate, nickel acetate, and nickel citrate.

[0009] The iron source is selected from one or more of the following: iron-based metal-organic framework materials, iron(II,III) oxide, ferric oxide, ferrous oxide, basic iron oxide FeO(OH), ferric hydroxide, ferrous hydroxide, ferrous sulfate, ferric sulfate, ferric nitrate, ferric acetate, ferric nitrate nonahydrate, ferrous nitrate, ferric chloride, ferric bromide, ferric phosphate, ferrous phosphate, ferric carbonate, ferric oxalate, ferrous oxalate, ferric acetate, ferric citrate, and ferrous citrate.

[0010] The manganese source is selected from one or more of the following: manganese-based metal-organic framework materials, manganese tetroxide, manganese trioxide, manganese monoxide, manganese oxide, manganese dioxide, manganese monohydroxymonoxide MnO(OH), hydrated manganese dioxide MnO(OH)2, manganese hydroxide Mn(OH)2, manganese carbonate, manganese sulfate, manganese nitrate, manganese acetate, manganese citrate, manganese oxalate, manganese formate, manganese acetate, and manganese phosphate.

[0011] The molar ratio of the nickel source, iron source and manganese source is preferably 1:1-2:1-2, and more preferably 1:2:2.

[0012] The mixing speed of the nickel source, iron source and manganese source is 600-1500 rpm, and the mixing time is 15-60 min. It is particularly preferred that the mixing speed is 1000 rpm and the mixing time is 30 min.

[0013] The second aspect of this invention is to provide a method for preparing a sodium-ion layered oxide cathode material, comprising the following steps: mixing the aforementioned nickel-iron-manganese oxide precursor with a sodium source and a blend T at a molar ratio to obtain a second mixture, and then sintering the second mixture in an air atmosphere at 500-1000°C for 15-30 hours to obtain the sodium-ion layered oxide cathode material.

[0014] The prepared sodium-ion layered oxide cathode material has the following structural formula: Na a Ni x Fe y Mn z T (1-x-y-z) O2, wherein 0.88 ≤ a ≤ 1.032, 0.15 ≤ x ≤ 0.2, 0.35 ≤ y ≤ 0.4, 0.35 ≤ z ≤ 0.4; T is a dopant element, wherein T is selected from at least one of Al, Cr, Co, Fe, Mg, Ti, V, Ni, Cu, Zn, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In, Sn.

[0015] Preferably: To further improve the specific capacity of sodium nickel iron manganese oxide, the sintering process adopts gradient sintering. The first sintering temperature is 500-850℃, the heating rate is 2-10℃ / min, and the time is 1-10 hours; the second sintering temperature is 850-1000℃, the heating rate is 2-10℃ / min, and the time is 12-20 hours.

[0016] Furthermore, the blend T, where T is a dopant element, is selected from at least one of Al, Cr, Co, Fe, Mg, Ti, V, Ni, Cu, Zn, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In, and Sn. The blend T can be at least one of the oxides, hydroxides, halides, sulfates, carbonates, nitrates, and nitrate oxides of the aforementioned dopant element.

[0017] The sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium oxalate, sodium acetate, sodium sulfate, sodium nitrate, sodium chloride, sodium sulfide, sodium citrate, sodium benzoate, sodium borate, sodium metaborate, and sodium tetrachloroborate.

[0018] Compared with the prior art, the present invention has the following advantages: (1) The preparation of sodium ion layered oxide cathode material using the nickel-iron-manganese oxide precursor is simple and easy to operate, with mild reaction conditions and relatively low manufacturing cost compared to the preparation of cathode material using traditional hydroxide precursors. Moreover, the product obtained has excellent performance and is suitable for large-scale production and application.

[0019] (2) The nickel-iron-manganese oxide precursor is prepared from at least two metal-organic framework materials selected from nickel, manganese and iron sources. After high temperature, the organic ligands inside the metal-organic framework material are removed to form a metal oxide precursor with a porous structure of nanoscale. This precursor is conducive to the diffusion of sodium ions during the sintering process after mixing, and also conducive to the doping of other elements in the cathode material. The sodium ion layered oxide cathode material prepared by this oxide precursor has better specific capacity and cycle performance. The particles of the oxide precursor prepared by this invention are more compact and rounded. The primary particles of the layered oxide cathode material after sintering by this oxide precursor are also compact and rounded, which reduces the negative reaction of the material interface during charging and discharging, effectively improves the structural stability of the material, and allows the specific capacity and cycle performance of the material to be fully utilized. Attached Figure Description

[0020] Figure 1 This is a SEM image of the nickel-iron-manganese oxide precursor prepared in Example 1 of the present invention.

[0021] Figure 2 This is a SEM image of the layered oxide cathode material prepared in Example 1 of the present invention.

[0022] Figure 3 This is a SEM image of the layered oxide cathode material prepared in Comparative Example 1 of this invention.

[0023] Figure 4 The images show the XRD patterns of the layered oxide cathode materials prepared in Comparative Example 1 and Example 1 of this invention.

[0024] Figure 5 The charge-discharge curves are shown for the layered oxide cathode materials prepared in Comparative Example 1 and Example 1 of this invention. Specific implementation methods

[0025] The present invention will now be explained in more detail through specific embodiments. However, it should be understood that the specific functional details disclosed in this specification should not be construed as limiting, but rather as the basis for the claims and as a representative basis for teaching those skilled in the art to employ the invention in different ways in any suitable detailed embodiment. Unless otherwise specified, the raw materials and reagents used in the embodiments are prior art or commercially available products.

[0026] In the following examples and comparative examples, nickel-based, iron-based, and manganese-based metal-organic framework materials were prepared using the following methods.

[0027] The preparation method of nickel-based metal-organic framework materials is as follows: The nickel source is Ni(CH3COO)2·4H2O, and the organic ligand is dihydroxyterephthalic acid. 0.989 g of the nickel source is dissolved in 5 mL of a mixed solution of ethanol and water (the volume ratio of ethanol to water in the mixed solution is 1:1) to obtain a nickel-containing solution. 0.308 g of the organic ligand is dissolved in 35 mL of N,N-dimethylformamide (DMF) solution to obtain an organic ligand solution. The organic ligand solution is poured into the above nickel-containing solution, stirred at room temperature for 25 minutes, and then placed in a polytetrafluoroethylene-lined hydrothermal reactor. The reactor is kept at 125 °C for 24 hours to obtain a precipitate. After washing and drying, the nickel-based metal-organic framework material is obtained.

[0028] The preparation method of iron-based metal-organic framework materials is as follows: The iron source is Fe(CH3COO)2·4H2O, and the organic ligand is dihydroxyterephthalic acid. 1.045 g of the iron source is dissolved in 5 mL of a mixed solution of ethanol and water (the volume ratio of ethanol to water in the mixed solution is 1:1) to obtain an iron-containing solution. 0.325 g of the organic ligand is dissolved in 35 mL of N,N-dimethylformamide (DMF) solution to obtain an organic ligand solution. The organic ligand solution is poured into the above iron-containing solution, stirred at room temperature for 25 minutes, and then placed in a polytetrafluoroethylene-lined hydrothermal reactor. The reactor is kept at 115 °C for 22 h to obtain a precipitate. After washing and drying, the iron-based metal-organic framework material is obtained.

[0029] The preparation method of manganese-based metal-organic framework materials is as follows: The manganese source is Mn(CH3COO)2·4H2O, and the organic ligand is dihydroxyterephthalic acid. 0.974 g of the manganese source is dissolved in 5 mL of a mixed solution of ethanol and water (the volume ratio of ethanol to water in the mixed solution is 1:1) to obtain a manganese-containing solution. 0.303 g of the organic ligand is dissolved in 35 mL of N,N-dimethylformamide (DMF) solution to obtain an organic ligand solution. The organic ligand solution is poured into the above manganese-containing solution, stirred at room temperature for 25 minutes, and then placed in a polytetrafluoroethylene-lined hydrothermal reactor. The reactor is kept at 135 °C for 24 h to obtain a precipitate. After washing and drying, the manganese-based metal-organic framework material is obtained.

[0030] Example 1

[0031] (1) Preparation of nickel-iron-manganese oxide precursor Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0032] Product characterization: like Figure 1 The image shown is a SEM image of the nickel-iron-manganese oxide precursor. This precursor is prepared from at least two metal-organic framework materials selected from nickel, manganese, and iron sources. After high-temperature treatment, the organic ligands inside the metal-organic framework materials are removed, forming a metal oxide precursor with a porous structure of nanoscale. This precursor is beneficial for the diffusion of sodium ions during the sintering process after mixing, and also facilitates the doping of other elements in the cathode material. The sodium ion layered oxide cathode material prepared from this oxide precursor has better specific capacity and cycle performance.

[0033] (2) Preparation of layered oxide cathode materials Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. The mixture was then sintered at 650℃ for 3 hours in air and then at 930℃ for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0034] Product characterization: SEM images of the prepared sodium ion layered oxide cathode material are shown below. Figure 2 As shown, the oxide precursor prepared by this invention has more dense and rounded particles. The primary particles of the layered oxide cathode material after sintering the oxide precursor are also dense and rounded, which reduces the negative reaction at the material interface during charging and discharging, effectively improves the structural stability of the material, and allows the specific capacity and cycle performance of the material to be fully utilized.

[0035] Example 2

[0036] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0037] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. The mixture was then sintered at 650 °C for 3 hours in air and then at 930 °C for 17 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0038] Example 3

[0039] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0040] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn zThe ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air and then at 930 °C for 15 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0041] Example 4

[0042] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0043] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650℃ for 3 hours in air and then at 910℃ for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0044] Example 5

[0045] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni.1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0046] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, and stirred at 1000 rpm to obtain a mixture. The mixture was sintered at 650 °C for 3 h in air atmosphere, and then sintered at 910 °C for 17 h. After sintering, it was naturally cooled to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 NixFeyMnzT 0.1 O2 (x+y+z=0.9).

[0047] Example 6

[0048] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0049] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, and stirred at 1000 rpm to obtain a mixture. The mixture was sintered at 650 °C for 3 h in air atmosphere, and then sintered at 910 °C for 15 h. After sintering, it was naturally cooled to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1O2 (x+y+z=0.9).

[0050] Example 7

[0051] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0052] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:6:3), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air, followed by sintering at 930 °C for 17 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0053] Example 8

[0054] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0055] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:6:3), based on the elemental molar ratio of Na:Ni x Fey Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air and then at 930 °C for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0056] Example 9

[0057] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0058] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 3:1:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air, followed by sintering at 930 °C for 17 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0059] Example 10

[0060] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0061] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 3:1:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air and then at 930 °C for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0062] Comparative Example 1

[0063] Referring to Example 1, the difference is that no element was doped in Comparative Example 1, thus the influence of doping elements on the morphology and properties of the material was examined. The preparation method is as follows:

[0064] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0065] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, in the elemental molar ratio Na:Ni x Fe y Mn zThe ratio of sodium ions to oxides was 1.025:1. The mixture was weighed and placed in a mixer, stirred at 1000 rpm to obtain a final product. This mixture was then sintered in air at 650°C for 3 hours, followed by sintering at 930°C for 19 hours. After sintering, the mixture was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z O2(x+y+z=1).

[0066] Product characterization: SEM images of the layered oxide cathode material prepared in Comparative Example 1 are shown below. Figure 3 As shown.

[0067] Comparative Example 2

[0068] Referring to Example 1, the difference is that: Comparative Example 2 investigated the effect of increasing the sintering temperature on the morphology and properties of the material. The preparation method is as follows:

[0069] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0070] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, blend T (a mixture of calcium carbonate, copper oxide, and zinc oxide, with an elemental molar ratio of Ca:Cu:Zn = 1:3:6), based on the elemental molar ratio of Na:Ni x Fe y Mn z The ratio of T = 1.025:0.90:0.1 was weighed and placed in a mixer, and stirred at 1000 rpm to obtain a mixture. The mixture was sintered at 650℃ for 3 hours in air atmosphere, and then sintered at 960℃ for 19 hours. After sintering, it was naturally cooled to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9).

[0071] Comparative Example 3

[0072] Referring to Example 1, the difference is that Comparative Example 3 only doped with Ca, and the effect of a single dopant element on the morphology and properties of the material was investigated. The preparation method is as follows:

[0073] Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0074] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, calcium carbonate, in elemental molar ratio Na:Ni x Fe y Mn z The ratio of Ca:1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air, followed by sintering at 930 °C for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9, T is Ca).

[0075] Comparative Example 4

[0076] Referring to Example 1, the difference is that Comparative Example 4 only doped with Cu, and the effect of a single doping element on the morphology and properties of the material was investigated. The preparation method is as follows: Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0077] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, copper oxide, in the elemental molar ratio Na:Nix Fe y Mn z The ratio of Cu:1.025:0.90:0.1 was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air, followed by sintering at 930 °C for 19 hours. After sintering, it was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9, T is Cu).

[0078] Comparative Example 5

[0079] Using Example 1 as a reference, Comparative Example 5, which only doped with Zn, investigated the effect of a single dopant element on the morphology and properties of the material. The preparation method is as follows: Nickel-based, iron-based, and manganese-based metal-organic framework materials were mixed in an elemental molar ratio of Ni:Fe:Mn = 1:2:2 at a rotation speed of 1000 rpm for 30 minutes, with the mixing temperature controlled below 50℃. The mixture was then subjected to solid-state sintering at 550℃ in air for 6 hours to obtain the nickel-iron-manganese oxide precursor Ni. 1 / 5 Fe 2 / 5 Mn 2 / 5 O2.

[0080] Ni, a precursor of nickel-iron-manganese oxide 1 / 5 Fe 2 / 5 Mn 2 / 5 O2, sodium carbonate, zinc oxide, in the elemental molar ratio Na:Ni x Fe y Mn z The Zn ratio (1.025:0.90:0.1) was weighed and placed in a mixer, where it was stirred at 1000 rpm to obtain a mixture. This mixture was then sintered at 650 °C for 3 hours in air, followed by sintering at 930 °C for 19 hours. After sintering, the mixture was allowed to cool naturally to room temperature, pulverized, and passed through a 200-mesh sieve to obtain the sodium ion layered oxide cathode material Na. 1.025 Ni x Fe y Mn z T 0.1 O2 (x+y+z=0.9, T is Zn).

[0081] Performance testing

[0082] Battery Assembly: The sodium-ion layered oxide positive electrode material prepared in the aforementioned examples and comparative examples was mixed with SP (conductive carbon black) and PVDF (polyvinylidene fluoride) at a mass ratio of 8:1:1. The PVDF was pre-prepared into a 4%wt PVDF solution using NMP (N-methylpyrrolidone) as a solvent. After stirring into a slurry, the slurry was coated onto a 15μm thick aluminum foil. The resulting electrode was dried, stamped, and pressed to form the sodium-ion battery positive electrode material. Using metallic sodium as the negative electrode and a PE separator with dimensions of 14μm × 60mm, the CR2016 button cell was assembled in an argon-filled glove box in the following order: positive electrode shell, positive electrode sheet, electrolyte, separator, sodium sheet, nickel mesh, electrolyte, and negative electrode shell.

[0083] After the battery was assembled, charge and discharge tests were performed. Under the voltage range of 2.0-4.0V, the battery was first cycled twice at 0.2C, and then the capacity and cycle performance were tested at 1C. The test results are shown in Table 1.

[0084] Table 1 .

[0085] As can be seen from Table 1: (1) Comparison of Examples 1-3 shows that the sodium ion layered oxide cathode materials prepared with different sintering times have different performance. The specific capacity of the first discharge at 0.2C current in Example 3 can reach 137.23 mAh·g. -1 After 100 cycles at 1C, the capacity retention rate reaches 90.42%. By adjusting the sintering time at 930℃ in the constant temperature zone, the first-cycle discharge specific capacity at 0.2C current in Example 1 reaches 138.56 mAh·g. -1 After 100 cycles at 1C, the capacity retention rate reaches 93.49%, which is the best performance.

[0086] (2) By comparing Examples 4-6, we can see the effect of changing the sintering temperature on the performance of sodium ion layered oxide cathode materials. Lowering the sintering temperature will affect the formation of primary single crystal particles, thereby affecting the cycle performance of the material.

[0087] (3) By comparison of Examples 7-10, it can be seen that in the preparation process of sodium ion layered oxide cathode material, when the proportion of zinc oxide in blend T is high, it is beneficial to the material capacity. When the proportion of copper oxide in blend T is high, it is beneficial to the improvement of cycle performance, but the material capacity is somewhat lost.

[0088] (4) Comparing Comparative Example 1 with Example 1, Example 1 was doped with multiple elements. Figure 2 This is a SEM image of the layered oxide cathode material prepared in Example 1. Figure 3The image shows a SEM image of the layered oxide cathode material prepared in Comparative Example 1. Comparing the two, the particle morphology of Example 1 is more rounded. Figure 4 A comparison of the XRD patterns of the two samples showed that the peak values ​​of 003 and 104 were higher in Example 1, indicating that the crystal formation of Example 1 was better. (Table 1 and...) Figure 5 Performance tests have also confirmed this.

[0089] The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a sodium-ion layered oxide cathode material, characterized in that, Includes the following steps: Nickel source, iron source and manganese source are mixed in a molar ratio, wherein at least two of the nickel source, iron source and manganese source are metal-organic framework materials to obtain a first mixture; then the first mixture is sintered in air at 400-850°C for 4-8 hours to obtain a nickel-iron-manganese oxide precursor. Nickel-iron-manganese oxide precursor is mixed with sodium source and blend T in molar ratio to obtain a second mixture. The second mixture is then sintered in air at 500-1000℃ for 15-30 hours to obtain sodium ion layered oxide cathode material. The prepared sodium-ion layered oxide cathode material has the following structural formula: Na a Ni x Fe y Mn z T (1-x-y-z) O2, wherein 0.88≤a≤1.032, 0.15≤x≤0.2, 0.35≤y≤0.4, 0.35≤z≤0.4; T is a dopant element, wherein T is selected from at least one of Al, Cr, Co, Fe, Mg, Ti, V, Ni, Cu, Zn, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In, Sn.

2. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The nickel source is selected from one or more of the following: nickel-based metal-organic framework materials, nickel tetroxide, nickel trioxide, nickel suboxide, basic nickel oxide, nickel hydroxide, nickel sulfate, nickel nitrate, nickel acetate, nickel chloride, nickel bromide, nickel phosphate, nickel phosphite, nickel carbonate, nickel oxalate, and nickel citrate.

3. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The iron source is selected from one or more of the following: iron-based metal-organic framework materials, iron(II,III) oxide, ferric oxide, ferrous oxide, basic iron oxide, ferric hydroxide, ferrous hydroxide, ferrous sulfate, ferric sulfate, ferric nitrate, ferric acetate, ferrous nitrate, ferric chloride, ferric bromide, ferric phosphate, ferrous phosphate, ferric oxalate, ferrous oxalate, ferric citrate, and ferrous citrate.

4. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The manganese source is selected from one or more of the following: manganese-based metal-organic framework materials, manganese tetroxide, manganese trioxide, manganese monoxide, manganese dioxide, hydrated manganese dioxide, manganese hydroxide, manganese carbonate, manganese sulfate, manganese nitrate, manganese acetate, manganese citrate, manganese oxalate, manganese formate, and manganese phosphate.

5. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The molar ratio of the nickel source, iron source and manganese source is 1:1-2:1-2.

6. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The mixing speed of the nickel source, iron source and manganese source is 600-1500 rpm, and the mixing time is 15-60 min.

7. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The sintering process employs gradient sintering. The first sintering temperature is 500–850℃, the heating rate is 2–10℃ / min, and the time is 1–10 hours. The second sintering temperature is 850–1000℃, the heating rate is 2–10℃ / min, and the time is 12–20 hours.

8. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The blend T is a dopant element selected from at least one of Al, Cr, Co, Fe, Mg, Ti, V, Ni, Cu, Zn, Zr, Nb, Mo, W, Ca, Y, La, Ce, Ga, In, and Sn. The blend T is also at least one of the oxides, hydroxides, halides, sulfates, carbonates, nitrates, and nitrate oxides of the dopant element.

9. The method for preparing a sodium-ion layered oxide cathode material according to claim 1, characterized in that: The sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium oxalate, sodium acetate, sodium sulfate, sodium nitrate, sodium chloride, sodium sulfide, sodium citrate, sodium benzoate, sodium borate, sodium metaborate, and sodium tetrachloroborate.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material precursor and preparation method thereof, sodium-ion battery positive electrode material, sodium-ion battery and electric equipment

    CN120483286A

  • Preparation method of metal oxide and application of metal oxide in lithium ion battery

    CN104355330A